Modeling the impact of floating oyster (Crassostrea virginica) aquaculture on sediment-water nutrient and oxygen fluxes - JM Testa (Inter-Research, 2015)
Bivalve aquaculture relies on naturally occurring phytoplankton, zooplankton, and detritus as food sources, thereby avoiding external nutrient inputs that are commonly associated with finfish aquaculture. High filtration rates and concentrated bivalve biomass within aquaculture operations, however, result in intense biodeposition of particulate organic matter (POM) on surrounding sediments, with potential adverse environmental impacts. Estimating the net depositional flux is difficult in shallow waters due to methodological constraints and dynamic processes such as resuspension and advection. In this study, we combined sediment trap deployments with simulations from a mechanistic sediment flux model to estimate seasonal POM deposition, resuspension, and processing within sediments in the vicinity of an eastern oyster Crassostrea virginica farm in the Choptank River, Maryland, USA. The model is the stand-alone version of a 2-layer sediment flux model currently implemented within larger models for understanding ecosystem responses to nutrient management. Modeled sediment-water fluxes were compared to observed denitrification rates and nitrite + nitrate (NO2-+NO3-), phosphate (PO43-) and dissolved O2 fluxes. Model-derived estimates of POM deposition, which represent POM incorporated and processed within the sediment, comprised a small fraction of the material collected in sediment traps. These results highlight the roles of biodeposit resuspension and transport in effectively removing oyster biodeposits away from this particular farm, resulting in a highly diminished local environmental impact. This study highlights the value of sediment models as a practical tool for computing integrated measures of nitrogen cycling as a function of seasonal dynamics in the vicinity of aquaculture operations.